Effect of brain death and non-heart-beating kidney donation on renal function and injury: an assessment in the isolated perfused rat kidney. - van den Eijnden, MM; Leuvenink, H; Ottens, P; 't Hart, N; van Oeveren, W; Morariu, A; van Goor, H; Ploeg, R (2003)
OBJECTIVES: Ischemic injury to the renal allograft prior to implantation is considered as the major cause of primary non and never-function (PNF) and delayed graft function (DGF). Evidence has been put forward that brain dead and non-heart-beating (NHB) donor organs are of marginal quality compared to living donors. The purpose of this study was to evaluate renal function and injury of brain dead and NHB donor kidneys using the isolated perfused rat kidney. MATERIAL AND METHODS: Fisher F344 rats were either maintained brain death for 4 hr or subjected to cardiac arrest for 45 min (NHB). Living rats served as controls. To omit additional effects of cold ischemia, kidneys were immediately reperfused. Renal function and injury were assessed by monitoring urine production, glomerular filtration rate (GFR), Na+ and K+ reabsorption, glucose metabolism and reabsorption, as well as release of brush border, lysosomal, and intracellular enzymes. RESULTS: Renal dysfunction and injury were most pronounced in NHB donor kidneys reflected by a highly reduced urine production, anaerobic glucose metabolism resulting in lactate formation, and significant higher luminal release of intracellular and lysosomal enzymes. Brain dead kidneys showed an increased urine production and were functionally abnormal in K+ reabsorption showing a net excretion of K+, probably as a result of ATP depletion. Loss of brush border occurred during brain death and cardiac arrest. CONCLUSIONS: Both, brain death and cardiac arrest have deleterious effects on renal function and renal injury. The ischemically injured NHB donor kidney was functionally inferior compared to the brain dead donor kidney and living donor kidneys. However, both brain dead and NHB kidneys showed considerable renal damage compared to kidneys from living donors.